Social functioning impairment in patients with depressive disturbances under war stress - Pyliagina Галина; Grinevich Євгенія; Mykhaylov Борис (Psychosomatic Medicine and General Practice, 2023)
The psychotraumatic factors that occurred during the war of 2022-2023 significantly affect the exacerbation / onset and manifestations of depressive syndrome (DS) in schizophrenia spectrum disorders (SSD) and neurotic depressive disorders (NDD), as well as worsen the level of social functioning (SF) of patients. Objective. To study the SF impairment in patients with DS in patients with SSD and NDD, and the relationship between the stress factors and the exacerbation of psychopathological symptoms and their severity in these patients. Methods and materials. There was conducted psychopathological examination of 92 patients with SSD (schizophrenia, Sch and schizoaffective disorder, SchAD) and neurotic DR (recurrent depression, RD and depressive reaction as adjustment disorders, AD) who experienced severe stress during the war. Results. In the research the largest number of patients were women (60.9% of cases). Among patients aged 18 - 25 years, majority of cases was the patients with AD (46.2%), in the group of 26 - 35 years - with SSD (50,0% with Sch and with SchAD). The vast majority of RD cases were presented among patients aged 36-50 years. Depressive syndrome significantly prevailed in patients with RD, and depressive-phobic syndrome in patients with AD. Whereas, depressive-delusional syndrome was most often diagnosed in patients with SSD. Among all examined patient’s reactive exacerbation of the main disease (in case of SSD and RD), as well as the development of RA occurred as a result of a significant impact of stress factors of different content, but related to the war in all cases.The most frequent of these were the feeling of "war fatigue", uncertainty and/or hopelessness about the future (in general 82% of patients with RD and RA); difficulties during evacuation, caused a strong increase in family conflicts, especially in patients with SSD (57.9% of cases in general) and RA; significant reduction of money for life. The impairment of SF in patients with various mental disorders and DS as a result of war-related stressors was mainly manifested in significant difficulty in daily professional and household duties (91.3% of all patients); the feeling of social support lacks and loneliness; frequent and/or prolonged interpersonal conflicts; as well as a strong financial problem. Other psychopathological features associated with DS that develop under the war stress influence and worsened the level of patients’ SF were sleep disturbances (97.8% of cases) with a significant direct correlation with a significant difficulty in daily activities; self-disbelief and hopelessness, as well as the emergence or strong increasing of suicidal thoughts were noted by more than 80% of the examined patients (36.0% of patients with NDDs had suicide attempts or self-injurirs - most often in AD); constant fatigue (80.0% of patients with NDDs). Conclusion. Understanding the impact of war-related stressors on the manifestations of DS, and the features and level of SF impairment need the use of treatment and rehabilitation complex for patients with DS (with SSD and NDD) who have experienced a severe psychotraumatic situation. It will allow timely and effective treatment of reactive states (relapses of psychotic episodes), take to account into the severity and characteristics of DS, and the content and severity of stressful effects in order to achieve remission, restore social adaptation of patients, and reduce the risk of self-destructive or aggressive behavior of them.